Analysis of The Shark Fisheries Sustainability in Cilacap Regency, Central Java - Anhar Muslim; Aristi Dian Purnama Fitri; Pujiono Wahyu Purnomo (Jurnal Perikanan dan Kelautan, 2019)
In terms of supporting sustainable fisheries management for sharks, information is needed so that the goals of sustainable management can be realized. In this case the management covers the ecological, economic, social and technological dimensions. The purpose of this study is to determine the sustainability status of Shark Fish based in Cilacap Regency based on ecological, economic, social and technological dimensions, determining the right strategy in sustainable shark fisheries management based in Cilacap Regency. This research was conducted from March to June 2018 in Cilacap Regency, this study used a survey method. Data collected related to the sustainability aspects of shark commodity fisheries in Cilacap Regency included ecological, technological, economic and social dimensions using questionnaire tools. Analysis for the sustainability of the Shark fisheries in Cilacap Regency The sustainability of shark fisheries in Cilacap Regency uses the Rapid Appraisal for Fisheries (RAPFISH) method. RAPFISH (Rapid Appraisal for Fisheries) was developed by Fisheries Center, University of British Columbia in 1999; Rapid Appraisal for Fisheries (RAPFISH) is a fisheries sustainability assessment method based on a multidimensional scaling approach. The dimensions in RAPFISH concern aspects of sustainability from ecology, economics, technology, social and ethics. Sustainability Status Multidimensional Shark Fisheries is less sustainable with a score of 43.28. The ecological dimension (56.56) and technology (55.51) is quite continuous, the economic dimension is less sustainable (45.63) and social conditions are unsustainable (15.42). The strategy for managing shark fisheries in Cilacap Regency is the W-T (Weakness-Threat) strategy.